A Single‐Cell Atlas of Crab Ovary Provides New Insights Into Oogenesis in Crustaceans - Li Lu; Tao Wang; An Liu; Haihui Ye (Advanced Science)
Abstract Oogenesis is crucial for sexual reproduction and provides the material basis for population continuation. Nonetheless, the identity of the cells involved, the nature of transformation, and underlying regulators of oogenesis in crustaceans remain elusive. Here, an atlas of the ovary is plotted via single‐nuclei RNA sequencing (snRNA‐seq) in the mud crab Scylla paramamosain, resulting in five cell types, including germ cells, somatic cells, and three follicle cell types identified, which in turn provides abundant candidate markers for them. Moreover, profiles of ligand‐receptor in different cells of the crab ovary indicate the roles of cell communication in oogenesis. Dozens of transcription factors in the trajectory from oogonia to oocytes as well as the key molecules/pathways in somatic cells and follicle cells relevant to oogenesis are screened, which is evolutionarily conserved and its underlying regulatory mechanism is subject to some modification across various phyla. The spatiotemporal expression patterns of seven markers are further verified and the RNAi confirms the essential roles of piwi and VgR in oogenesis. These data help to elucidate the mechanism underlying gametogenesis and the evolution of reproductive strategy in invertebrates.